Проблема гнуса в зонах влияния крупных водохранилищ Украины - Шевченко, A.К.; Стеблюк, М.В. (Вестник зоологии, 1974)
Qualitative and quantitative changes in blood-sucking flies composition as well as redistribution of places of their development in certain big reservoirs of the Ukrainian SSR are shown. Changes in blood-sucking flies development for above 10 years exploitation of the Krasnooscolian reservoir are analyzed. An effect of new environmental conditions on the species ecology or species and subspecies composition of flies is illustrated by series of examples.